Comparative antioxidant and bioavailability studies of Vitamin C in Phyllanthus emblica Linn. and its combinations with Piper nigrum Linn. and Zingiber officinale Roscoe (Brazilian Journal of Pharmaceutical Sciences, 2016)
Phyllanthus emblica Linn. (amla) is used in Ayurveda, the ancient Indian system of medicine and its major constituent is vitamin C which has effective free radical scavenging property. The purpose of this study was to evaluate the in vitro antioxidant activity and the bioavailability profile of vitamin C in amla and its combinations with piperine and ginger in comparison to synthetic vitamin C using New Zealand rabbits. In vitro antioxidant activity studies of synthetic vitamin C, amla, amla with piperine and amla with ginger were carried out using different models such as 2,2-Diphenyl-1-picrylhydrazyl, Nitric Oxide, Hydrogen peroxide scavenging methods, Total reductive capability and Oxygen Radical Absorbance Capacity estimation. The study results showed that synthetic vitamin C, amla, amla with piperine and amla with ginger possess significant in vitro antioxidant activity. For bioavailability studies, synthetic vitamin C, amla, amla with piperine and amla with ginger 100 mg/kg, were administered orally and the serum samples were analyzed by HPLC at 0, 1, 2, 3, 4, 6, 8, 10, 12 and 24 hours. Bioavailability studies revealed that amla with piperine combination has higher concentration of vitamin C when compared to synthetic vitamin C. This is probably due to presence of piperine, which is a bioavailability enhancer. The present study supports the fact that amla with piperine combination can be an alternative to synthetic vitamin C.